Respuesta :

Answer:  9

========================================================

Explanation:

Recall the standard form of a quadratic is ax^2+bx+c

The 'b' is the coefficient of the x term. In this case, b = -6

Cutting that in half yields b/2 = -6/2 = -3

Then squaring that result gets us (b/2)^2 = (-3)^2 = 9

We must add 9 to both sides to complete the square.

--------

Extra info (optional section):

If we added 9 to both sides, we could then say the following

1 = x^2 - 6x

1+9 = x^2 - 6x + 9

10 = (x - 3)^2

(x-3)^2 = 10

Which would be useful to apply the square root rule to help isolate x.

ACCESS MORE